(untitled) (Experimental biology, 2015)
In the study of blood immunological parameters in workers of sugar factory, farm, as well as teachers of the Almaty oblast it was found that the sugar factory workers regardless of sex, had an increase in serum γ-interferon, immunoglobulin G and interleukin-2 content as compared to other surveyed groups